Normalising childbirth in women living with HIV: a London teaching hospital experience. (18th April 2012) - Kojeku, A; Handrahan, C; Marshall, N; Levitt, D; Kinloch, S; Johnson, M
Abstract : Introduction: Over the past 15 years there has been a significant reduction in the incidence of HIV-1 mother-to-child-transmission (MTCT) despite increasing prevalence of diagnosed HIV-1 infection during pregnancy across England and Scotland (0.2% in 2008), particularly in London (0.4%). Objective: To assess the management of HIV pregnant women in a London Teaching Hospital. Method: A retrospective review of HIV positive women who delivered from January 2008 to November 2011. Results: At the time of submission, data was available for 56 women (59 pregnancies). 75% of women were born in sub-Saharan Africa. 5 women were diagnosed antenatally. All the women had multidisciplinary antenatal care by a specialist team. They were all on HAART therapy and had regular Liver Function Tests (LFT), second trimester GTT as well as STD screening. 17% (n=10) had an abnormal LFT result at some point during the pregnancy. 2 of these women had documented positive Hepatitis serology (HBV). 88% (n=53) had undetectable viral load at delivery. 46% (n=27) achieved a vaginal delivery. 12% (n=7) were delivered by elective Caesarean section for detectable viral load whilst the remainder were for Obstetric reasons. 15% had emergency Caesarean section one of which was for suspected uterine rupture. There were no significant maternal complications. None of the babies tested positive for the virus and there was no documented report of teratogenicity. Conclusion: Our management of HIV positive women has successfully enabled women to labour as well as deliver with minimum intervention with a zero vertical transmission.